The continuous search for new port governance models: Experiences from a developing country - Torben Andersen; Jonas Aryee; George Acheampong; Annette Skovsted Hansen (Journal of Shipping and Trade (JST), 2023)
This paper bridges port governance and stakeholder theory to contribute to new understandings of changed stakeholder relations due to the building of new container terminals. The case of the newly inaugurated very large high-tech container terminal commissioned to and developed and operated by Meridian Port Services (MPS), in the Port of Tema, Ghana, provides the empirical foundation for investigating the new stakeholder engagement. Through focus groups, descriptive statistics, and a series of qualitative and open-ended interviews carried out in structured stakeholder events, the paper aims to deliver new knowledge relevant to the many hybrid port governance systems seen today. Moreover, it wants to inform authorities and companies about the implications of different strategic choices and how changes progress. The study shows that despite shared goals of efficiency, all parties involved have had major difficulties in finding a new port governance model, which they all consider fair and which can contribute to a continuously economically sustainable port management practice.
Keywords: 650; Inclusive port development; Port governance; Stakeholder theory